Mathematical modelling of the process of natural gas transportation via pipe networks using crossing-branch method (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2024)
This research is among the most relevant research on the problems of natural gas transportation through pipeline networks. The increased demand for natural gas in Kazakhstan is associated with a greater level of environmental friendliness; as a result, many power generating stations use natural gas as their main source of energy. Modernization of existing thermal power plants is necessary to improve the environmental situation in the country. There are three main groups of gas pipeline systems considered in the literature: collection, transmission, and distribution systems. In this article, we present detailed research on the transmission process and develop useful approaches. Over the past few years, a huge amount of research has been conducted on many problems of decision-making in the gas industry and, in particular, on optimizing the pipeline network. In this paper, we consider dynamical models, highlighting aspects of modelling and the most relevant solutions to date. This research can serve as a useful tool for understanding the evolution of many real-world applications and the most recent advances in solution methodologies emerging in this complex field of research. The results of this research can be used to develop technologies for automating calculations, planning, and optimizing natural gas transportation.